Chapter Body, Spirit and Gender in Anne Conway - Felter, Karen (Aschendorff Verlag, 2024)
The relation between body and spirit is a central topic in Lady Anne Conway’s (1631–1679) treatise The Principles of the Most Ancient and Modern Philosophy: